The nature and construction of Chinese nationalism towards Japan: through the lens of the Diaoyu/Senkaku case study, 2010 and 2012 - Burcu, Oana (2017)
In the last two decades, against the backdrop of multiple anti-foreign protests in China, among which the anti-Japanese protests were prominent, debates emerged over the rise and meaning of Chinese nationalism. This thesis analyses the nature and formation of China’s nationalism towards Japan, with an emphasis on bottom-up manifestations of nationalism. The analysis compares the anti-Japanese demonstrations and boycotts of 2010 and 2012 triggered by disputes over the contested Diaoyu/Senkaku islands in the East China Sea.